(untitled) (Zona Laut Jurnal Inovasi Sains Dan Teknologi Kelautan, 2022)
The 70 GT multipurpose fishing vessel is a type of vessel designed to operate longer at sea. This ship has a relatively wider cargo space with a variety of fishing gear (multipurpose). The ship is propelled by a 283 kW diesel engine and the source of electric power is supplied by a 20 kW diesel generator. The purpose of this study is to determine the amount of electric power used for ship lighting. The method used is the lumen method or the zonal cavity method. This method is used to determine the proper lighting standards on board according to regulatory standards from the American Bureau of Shipping (ABS) class. The results of the study showed that the total electric power needed for lighting on board was 0.4 kW. LED lights are an alternative in determining the type of lighting that is energy efficient and durable on board.-